2017
DOI: 10.1097/rct.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bile Reflux Gastritis and Biliary Excreted Contrast Media in the Stomach

Abstract: Biliary excreted contrast media in the stomach on 60-minute delayed gadoxetic MRC has a correlation with the presence of bile reflux gastritis on endoscopic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Bile is thought to be the main duodenal component. Bile reflux has been found to be closely related to upper gastrointestinal inflammation, development of ulcers, intestinal metaplasia and carcinoma 10‐12 . A previous study of 2283 patients found that high levels of bile acid reflux were linked to an increased risk of intestinal metaplasia 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile is thought to be the main duodenal component. Bile reflux has been found to be closely related to upper gastrointestinal inflammation, development of ulcers, intestinal metaplasia and carcinoma 10‐12 . A previous study of 2283 patients found that high levels of bile acid reflux were linked to an increased risk of intestinal metaplasia 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Bile reflux has been found to be closely related to upper gastrointestinal inflammation, development of ulcers, intestinal metaplasia and carcinoma. [10][11][12] A previous study of 2283 patients found that high levels of bile acid reflux were linked to an increased risk of intestinal metaplasia. 12 Thus, we hypothesized that bile reflux might play an important role in the occurrence and development of GC and precancerous lesions.…”
mentioning
confidence: 99%
“…Several studies reported that bile reflux was associated with reflux esophagitis, the proliferation of esophageal squamous cells, Barrett's adenocarcinoma, and intestinal metaplasia in the cardia (19,20). Moreover, recent studies suggested the association between bile acids and the risk of precancerous gastric lesions such as atrophic gastritis and intestinal metaplasia (3,7,21). Matsuhisa et al demonstrated that the total bile acid concentration was correlated with the grade of glandular atrophy and intestinal metaplasia of the stomach (3,22).…”
Section: Discussionmentioning
confidence: 99%
“…Refluks bile ke gaster ini dapat menyebabkan bile reflux gastritis. 1 Bile reflux gastritis merupakan gastritis atau inflamasi pada mukosa gaster yang disebabkan oleh paparan cairan empedu dan isi duodenum ke gaster. 2,3 Bile reflux gastritis merupakan kondisi klinis yang jarang dikenali pada praktik klinis.…”
Section: Pendahuluanunclassified
“…Salah satu penelitian menunjukkan bahwa dari pasien-pasien yang menjalani endoskopi, terdapat sekitar 10% pasien mengalami duodenogastric reflux. 1 Di Indonesia, kasus bile reflux gastritis jarang dilaporkan. Kasus pernah dilaporkan di Padang yaitu sebanyak 11,53% dari total pasien endoskopi selama tahun 1981 sampai 1983.…”
Section: Pendahuluanunclassified